Public health communication: Attitudes, experiences, and lessons learned from users of a COVID-19 digital triage tool for children - Michel, Janet; Rehsmann, Julia; Mettler, Annette; Starvaggi, Carl; Travaglini, Nicola; Aebi, Christoph; Keitel, Kristina; Sauter, Thomas C. (Frontiers in Public Health, 2022)
Background: The pandemic has made public health communication even more daunting because acceptance and implementation of official guidelines and recommendations hinge on this. The situation becomes even more precarious when children are in involved. Our child specific COVID-19 online forward triage tool (OFTT) revealed some of the public health communication challenges. We aimed to explore attitudes, experiences and challenges faced by OFTT users and their families, in regard to public health recommendations. Methods: We selected key informants (n=20) from a population of parents, teachers, guardians as well as doctors who had used the child specific COVID-19 OFTT, and had consented to a further study. Video rather than face-face interviews were held. Convenience and quota sampling were performed to include a variety of key informants. Interviews were recorded, transcribed verbatim and analysed for themes. Results: Several themes emerged namely; (1) definition and expectations of high-risk persons (2) quarantine instructions and challenges (3) blurred division of responsibility between authorities and parents (4) a novel condition and the evolution of knowledge, (5) definition and implications of socio-economic status (6) new normal and societal divisions and (7) the interconnectedness of these factors-systems thinking. Conclusion: As the virus is evolving and circumstances are changing rapidly, the communication of public health to the different interest groups, becomes both an art and science, even more so when using a new technological communication channel: an OFTT. A myriad of interconnected factors seems to influence attitudes towards public health recommendations, which calls for systems thinking in public health communication